2019
DOI: 10.1002/naaq.10120
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Physiology and Stress Responses of Pellet‐Reared Largemouth Bass Fed Live‐Forage Diets

Abstract: Advanced-sized Largemouth Bass Micropterus salmoides to be used for stocking and experimentation can be efficiently reared on prepared feed in intensive culture conditions, but formulated diets containing high levels (≥20%) of dietary carbohydrates may lead to high liver and muscle lipid and high liver glycogen levels, which may affect survival and stress responses. Largemouth Bass were raised to a size of 240-344 mm TL on formulated diets and then were fed live forage (i.e., naturalization); the effects of na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…Rearing of river stocking materials to larger sizes often has unintended adverse effects. When unscientifically chosen feed is used, there is a high chance of nutritional deficiencies or morphological alterations [ 56 , 57 , 58 , 59 ]. Although morphological alterations are visible to the naked eye, physiological alterations or deficiencies in the body’s nutrients pool remain subtle.…”
Section: Discussionmentioning
confidence: 99%
“…Rearing of river stocking materials to larger sizes often has unintended adverse effects. When unscientifically chosen feed is used, there is a high chance of nutritional deficiencies or morphological alterations [ 56 , 57 , 58 , 59 ]. Although morphological alterations are visible to the naked eye, physiological alterations or deficiencies in the body’s nutrients pool remain subtle.…”
Section: Discussionmentioning
confidence: 99%
“…Fish were raised on a formulated diet (EXTR 450; 46% protein, 20% carbohydrates, 16% fat; Rangen, Inc., Buhl, Idaho) using the methods described by Dinken et al. (2020).…”
Section: Methodsmentioning
confidence: 99%
“…This process, TEMPERATURE AND ANGLING EFFECTS ON STRESS RESPONSE termed "naturalization," was used to reduce the physiological effects of high dietary carbohydrates on liver function (Goodwin et al 2002;Amoah et al 2008) and to improve overall health. A separate experiment found that a naturalization period of 4-6 weeks reduced many of the negative effects of high (20%) carbohydrate diets on liver health and physiology (Dinken et al 2020), and fish had high survival after a 60-s chasing stressor .…”
Section: Specimensmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the expected effects of size on stocked fish survival, it is not surprising that fishery managers have recognized the benefits of advanced sizes to the supplemental stocking of Largemouth Bass (Hoxmeier and Wahl 2002; Porak et al 2002; Colvin et al 2008; Mesing et al 2008; Diana and Wahl 2009). In some cases, however, rearing Largemouth Bass to larger sizes may incur unintended negative effects, such as morphological alterations (Wintzer and Motta 2005) or, if pelleted feed is used, nutritional deficiencies (Porak et al 2002; Cardeilhac et al 2008; Dinken et al 2019). Together, these studies have suggested that size at stocking should matter and that generally larger stocked Largemouth Bass should be more likely to increase fish populations, but managers will face trade‐offs with production numbers and influences of rearing techniques.…”
mentioning
confidence: 99%